GIS-Based Spatial Equity Assessment of Temporary Waste Disposal Sites in Riverbank Informal Settlements: A Case Study of Palembang, Indonesia - Saputra, Wahyu; Aryaningrum, Kiki; Pujianto; Sukmaniar; Rhamadan, Muhammad Qobul Ridho (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Rapid population growth and urbanization in informal settlements along the Musi Riverbank, Palembang City, have intensified pressure on the waste management system, particularly due to the uneven distribution of Temporary Disposal Sites (TPS) and limited collection services. This study, conducted in June–July 2025, examines the spatial conditions of TPS and waste management through a quantitative methods approach that integrates Geographic Information Systems (GIS) with a survey of 385 respondents across 13 sub-districts. Results indicate that TPS facilities remain concentrated in densely populated areas, while Gandus and Kertapati exhibit substantial service gaps, with 63.1% of residents unaware of any TPS near their area and 20.3% reporting inadequate TPS availability. Spatial analysis shows that only 34.0% of households live within 0–0.5 km of a TPS, while 24.4% are located more than 1 km away, indicating significant underserved zones. The study recommends GIS-based TPS redistribution and stronger community engagement mechanisms as actionable strategies to support evidence-based municipal waste planning and policy.